Impact of Herbal Mix Incorporation on Biscuit Attributes: Impact of herbal mix on biscuit quality - Anuj Kumar,; Sharma, Gopal Kumar; Vashishth , Rahul; Semwal, Anil Dutt; Devi , Hanjabam Mandakini (Journal of Cereal Research, 2025)
The increasing popularity of foods possessing additional health benefits has set new demands for snack foods including biscuits. These novel snacks while maintaining basic nutritional benefits, should also exhibit additional health benefits. Along these lines, the biscuit was utilized as a carrier for herbal-mix consisting of tulsi, ginger, and black pepper. The baking combination of 190°C for 10 min and herbal blend having ginger, tulsi and black pepper in the ratio of 5:2:1 was standardized after preliminary experimentation. Herbal mix and honey concentration in biscuits were optimized employing a two-factor response surface methodology experiment based on central composite rotatable design. The optimal formulation of biscuits could be prepared using 6.38 parts herbal-mix and 55 parts honey. In comparison to control biscuits, functional biscuits had significantly (p